Screen Position Preference Offers a New Direction for Action Observation Research: Preliminary Findings Using TMS - Riach, Martin; Wright, David J.; Franklin, Zoë C.; Holmes, Paul S. (Frontiers in Human Neuroscience, 2018)
Action observation has been suggested to be an effective adjunct to physical practice in motor (re)learning settings. However, optimal viewing conditions for interventions are yet to be established. Single-pulse transcranial magnetic stimulation (TMS) was used to investigate the effect of two different screen positions and participants’ screen position viewing preference on the amplitude of motor evoked potentials (MEPs) during observation of a ball pinch action. Twenty-four participants observed four blocked conditions that contained either a dynamic index finger-thumb ball pinch or a static hand holding a ball in a similar position on a horizontally or vertically positioned screen. TMS was delivered to the hand representation of the left primary motor cortex and MEPs were recorded from the first dorsal interosseous muscle of the right hand. Initial analysis of the normalised MEP amplitude data showed no significant differences between conditions. In a follow-up procedure, participants engaged in individual semi-structured interviews and completed a questionnaire designed to assess viewing affect and screen position viewing preference. The MEP data were subsequently split by screen position preference and re-analysed using a 2x2 repeated measures ANOVA. Main effects indicated that participants who preferred the horizontal screen position (n=16) demonstrated significantly greater MEP amplitudes during observation of the ball-pinch action compared to the static hand condition irrespective of screen position, and during the horizontal compared to the vertical screen position irrespective of video type. These results suggest that ensuring anatomical and perceptual congruency with the physical task, alongside consideration of participants’ screen position viewing preferences, may be an important part of optimising action observation interventions.